Injury risk factors in youth alpin ski racing - A narrative review - Steidl-Mueller, L.; Hildebrandt, C.; Mueller, E.; Raschner, C. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Alpine ski racing is known to be a sport with a high risk of injuries (Spörri et al., 2017). Additionally, it is a late specialization sport and the peak performance in elite alpine ski racing is mostly achieved between the ages of 26 to 28 years (Raschner et al., 2013). The specialization at an early age combined with a long athlete`s competitive life needs to be considered when implementing strategies to develop talents. Therefore, skiing specific injuries are of particular interest, especially also in growing athletes (Steidl-Müller et al., 2019). The knee is the most affected body part at both World Cup level (35.6%; Spörri et al., 2017) and youth level with athletes youngerthan 15 years of age (36.5%; Müller et al., 2017a). However, at World Cup level, the rupture of the anterior cruciate ligament (ACL) is the most frequent reported diagnosis of all injuries (13.6%; Florenes et al., 2009), whereas this medical problem is less severe at the youth level. Among 67 youth ski racers aged 10 to 14 years only two ACL ruptures were reported over the period of two seasons (Steidl-Müller et al., 2018). It can be assumed that the elastic properties of tendon structures in the growing athlete are higher and thus, more compliant compared to full-grown athletes (Kubo et al., 2001). At youth level, though, a relatively high number of bone fractures including physeal fractues was observed. A fact that was explained by two reasons: first, the age of peak bone mass is later than age at peak height velocity (APHV) by up to one year, which could lead to a higher vulnerability to bone fractures in athletes younger than 16 years (Müller et al., 2017a). Second, the physis is weaker than ligaments, and therefore, fractures are more likely to occure compared to ruptures (Müller et al., 2017a). Due tothe diverse nature of skiing specific injuries occurring at youth levels compared to the elite level, it is absolutely necessary to identify injury risk factors for youth ski racers younger than 15 years, in order to be able to elaborate injury prevention measures for this specific age group with the main aim of contributing to injury-free long term careers. Until 2017, the main emphasis in injury prevention research in alpine ski racing was placed on top level athletes and mainly on traumatic injuries. Whereas, injuries at the youth level and overuse injuries were rarely investigated. During the last few years, research in youth ski racing (athletes aged 10-14 years) concentrated mainiy on four possible aspects of injury risk factors: 1) anthropometric characteristics and biological maturity status, 2) relative age, 3) physical fitness Parameters and asymmetries, and 4) training load characteristics and ski racing technique.